Hubungan Pertukaran Pemimpin-Pengikut, Kepuasan Kerja Dan Komitmen Organisasional - Ariani, D Wahyu (208-7721)
This study examined the relationship between leader-member exchange, job satisfaction, and organizational commitment in service industry. Following social exchange theory and role theory, we compete three relationship models. Resuls from correlation and regression study with 430 respondents ofÂ  service industry indicate that leader-member exchange, job satisfaction, continuance organizational commitment are the predictors of affective organizational commitment in service industry.